2007
DOI: 10.1159/000108315
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alteration associated with chronic lymphocytic leukemia

Abstract: The genetics of B-cell chronic lymphocytic leukemia (B-CLL) differ considerably from most other forms of hematologic malignancy which are usually characterized by chromosome translocations. B-CLL typically contains chromosomal deletions and chromosomes 13q14 and 11q22→q23 are the most common. These two regions appear to share a common ancestral origin (Auer et al., 2007b). Overall, chromosomal abnormalities can be found in the majority of patients with B-CLL when using sensitive techniques (Dohneret al., 2000)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 247 publications
1
19
0
Order By: Relevance
“…The consensus minimally deleted region for 13q14 is approximately 600 kb between chromosomal locations D13S273 and D13S25. 15 However, various reports describe smaller regions in the 350 to 550 kb range 18 -20 based largely on observations from one or two cases. The ϳ600 kb consensus 13q14 minimally deleted region has 79 SNPs on 250K Nsp array within that region.…”
Section: K Nsp Array Provides Adequate Resolution For Cll Prognostmentioning
confidence: 99%
“…The consensus minimally deleted region for 13q14 is approximately 600 kb between chromosomal locations D13S273 and D13S25. 15 However, various reports describe smaller regions in the 350 to 550 kb range 18 -20 based largely on observations from one or two cases. The ϳ600 kb consensus 13q14 minimally deleted region has 79 SNPs on 250K Nsp array within that region.…”
Section: K Nsp Array Provides Adequate Resolution For Cll Prognostmentioning
confidence: 99%
“…However, it is unlikely to be the sole cause of the 11q abnormality, as the minimally deleted region of 11q houses other potential candidate TSGs, such as RDX and FDX1 genes, 20 and not all CLL patients with deletions of 11q have evidence of an ATM mutation of the remaining allele. 21 Other groups have reported data suggesting that there is a slightly more telomeric but overlapping region that does not include ATM. [21][22][23] This finding was corroborated by Lehmann et al 5 who also observed a second commonly deleted region at 11q that is telomeric to the ATM gene when they used SNP arrays to karyotype CLL samples.…”
mentioning
confidence: 99%
“…21 Other groups have reported data suggesting that there is a slightly more telomeric but overlapping region that does not include ATM. [21][22][23] This finding was corroborated by Lehmann et al 5 who also observed a second commonly deleted region at 11q that is telomeric to the ATM gene when they used SNP arrays to karyotype CLL samples. It is postulated that this region may harbor another TSG associated with the development of CLL, and that concurrent deletion of ATM and this other TSG may contribute to a poor prognosis.…”
mentioning
confidence: 99%
“…Although CLL is usually characterised by chromosomal deletions (Cotter and Auer, 2007), ALL and many other forms of leukaemia usually harbour chromosomal translocations in a significant number of transformed cells. Despite the extensive sequencing analysis over the last decade, no major point mutations have been identified in CLL or ALL.…”
Section: Resultsmentioning
confidence: 99%
“…Chromosome defects are the most common genetic abnormalities seen in CLL, and the last decades have seen much progress in delineating the role of these genetic aberrations in the pathogenesis of CLL (Cotter and Auer, 2007). However, the genetics of CLL is still not fully understood.…”
mentioning
confidence: 99%